The Universe Had One Chance. Issue 2 (April 2016) - Demarest, Heather
Abstract : In a deterministically evolving world, the usefulness of nontrivial probabilities can seem mysterious. I use the 'Mentaculus' machinery developed by David Albert and Barry Loewer to show how all probabilities in such a world can be derived from a single, initial chance event. I go on to argue that this is the only genuine chance event. Perhaps surprisingly, we have good evidence of its existence and nature. I argue that the existence of this chance event justifies our epistemic reliance on nontrivial probabilities.